Differential response of roots growth of soybean germplasm under low pH and manganese toxicity - HERU KUSWANTORO (Society for Indonesian Biodiversity, 2017)
Abstract. Kuswantoro H. 2016. Differential response of roots growth of soybean germplasm under low pH and manganese toxicity. Biodiversitas 18: 257-262. Most of Indonesia dry land are covered by acid soil. The growth and development of the plant in this acid soil cope with low pH and micronutrients toxicity. The objective of this research was to study the response of root growth of soybean germplams to low pH and manganese toxicity. Nine soybean germplasm were treated in aquadest with pH 7 as control, aquadest with pH 4, and 75 ppm Mn with pH 4 in Seed Laboratory of Indonesian Legume and Tuber Crops Research Institute, Malang, Indonesia. Results showed that root length, number of lateral roots, root dry weight were lower in low pH and Mn toxicity than in the control. Shoot dry weight, hypocotyl length and epicotyl length were not influenced by low pH and Mn toxicity. Some genotypes showed increasing root length in low pH, and increasing number of lateral roots and root dry weight in Mn toxicity. Based on the acid soil adaptation index (ASAI) on root length, MLGG 0493 and MLGG 0496 showed the highest value index in three comparative conditions. The genotype of MLGG 0496 also showed the highest ASAI value on numbers of lateral root in three comparative conditions. MLGG 0494 achieved the highest ASAI value of root dry weight. However, the use of root dry weight as a criterion in soybean adaptation in low pH and Mn toxicity should be studied further because the tolerance is not just in increasing root dry weight as a result of root thickening. Keywords: ASAI, germplasm, low pH, Mn toxicity, root growth, soybean